Signos e Metáforas na Comunicação da Música - Oliveira, Luciana David de (2007)
The key questions that triggered this research were: does music communicate anything? what does it communicate? is that communication metaphorical? The communication theme in music, which is a non-verbal language and, perhaps, the most intransitive of the arts through its evident independence in relation to the factic world and intense vagueness of its object, will be approached in this dissertation having Peirce s Semiotics as a tool, not only for epistemological support, but, also, to represent the theoretical kernel of the phenomenon of communication. In the first chapter we will present a synthesis of the evolution of musical language, seen through the history of music and through Semiotics, highlighting the application of this science to music. In the second chapter, with the help of José Luiz Martinez, Ivo Assad Ibri and Lucia Santaella, we will delve into Peirce s Semiotics with the aim of placing it in the context of Peirce s larger theoretical edifice, proceeding to its subsequent application to the object of research, encompassing the identification of the kinds of signs, objects and interpretants in the music millieu. In the third chapter, with the aid of theoretical tools honed by Ivo Ibri and Carl Hausman, emphasis will be given to the question of the object of music and its iconic, polissemic and metaphorical character, under a more philosophical viewpoint, with the intention of understanding, through Peirce s categorical symmetry, how the dynamical object originates in the mind of the listener through the use of metaphors. These, being third of firstness signs, supply meaning to music, besides being fundamental to close the semiotic triad sign-object-interpretant. In the last chapter, Peirce s Semiotics will consubstantiate a semiotic analysis of Heitor Villa-Lobos Bachianas Brasileiras # 4 , whose choice derived from the fact that this music piece is a metaphorical sign both in Bach s opus and in Brazilian music, something that makes the understanding of the metaphor a lot easier, that is, in the light of the theoretical system previously exposed, as being a relation of meanings that merge in the mind of the interpretant, thus producing something new. All this research work and the subsequent application of the theories makes one realize how much music communicates through the action of signs and the creation of metaphors